The Effect of Alumni Sharing Sessions on Enhancing Academic Motivation of Students at Universitas Andalas - Roni Saputra; Okky Adelirandy; Roni Ekha Putera; Fachrur Rozi (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
Academic motivation provided an important role in students’ academic success and career preparation; however, many university students experience motivational decline due to uncertainty about future career pathways. This study examined the effect of alumni sharing sessions on academic motivation and career-related outcomes among undergraduate students at Universitas Andalas. A quantitative pre–post design was applied involving 44 undergraduate students who participated in an alumni sharing session. Data were collected using measures of academic motivation, career decision-making self-efficacy, job-search intention, and perceived study–work relevance. Descriptive analysis and Wilcoxon signed-rank tests were conducted to examine changes before and after the intervention. The results showed no statistically significant change in overall academic motivation. However, significant improvements were found in intrinsic motivation and identified regulation, accompanied by a significant decrease in amotivation. Career decision-making self-efficacy increased significantly after the session, while job-search intention and study–work relevance demonstrated positive directional changes. Participants also rated the alumni sharing session as beneficial for clarifying career direction and strengthening learning relevance. These findings suggest that alumni sharing sessions contribute meaningfully to strengthening specific dimensions of academic motivation and enhancing career readiness among university students.